Dynamic expression of the pro-dopaminergic transcription factors Pax6 and Dlx2 during postnatal olfactory bulb neurogenesis - de Chevigny, Antoine; Core, Nathalie; Follert, Philipp; Wild, Stefan; Bosio, Andreas; yoshikawa, Kazuaki; Cremer, Harold; Beclin, Christophe (Frontiers in Cellular Neuroscience, 2012)
Olfactory bulb neurogenesis generates neurons that use GABA, dopamine or glutamine as their neurotransmitters throughout life. Regionalized stem cell populations in the periventricular zone (PVZ) of the lateral ventricles have been shown to be at the basis of neuronal diversity in the system. For example dopaminergic neurons arise predominantly from neural stem cells residing in the dorsal PVZ and depend on the expression of the transcription factors Pax6 and Dlx2 for their specification. In addition Dlx2 is required for neurogenesis in general. Using targeted in vivo electroporation combined with immuno-fluorescence imaging and micro-array analysis, we provide here detailed spatial and temporal expression data with cellular resolution in this system. We find that all along the neurogenic process Pax6 expression remains restricted to the dorsal PVZ, whereas nearly all neuroblasts express Dlx2, including those of the dorsal lineage which are switched on for Dlx2 when they enter the RMS. These data allow to explain and precise the functions of these 2 genes in post-natal olfactory bulb neurogenesis.